Determining factors of entrepreneurial intention: a study with entrepreneurs and potential entrepreneurs of the state of Acre - Brito, Bárbara Alessandra Vieira de; Kuniyoshi, Márcio Shoiti; Cappellozza, Alexandre; Vieira, Almir Martins (Revista de Administração da UFSM, 2022)
Objectives - this article aimed to analyze, from the perspective of the Theory of Planned Behavior, the determining factors of the entrepreneurial intention of entrepreneurs and potential entrepreneurs of Acre. Design / Methodology / Approach - The research covered graduates of the Empretec Seminar (SEBRAE), using the quantitative methodology of Structural Equation Modeling by Partial Least Square Structural Equation Modeling (PLS-SEM). Results - Results showed that Attitude Towards Behavior is the construct that most positively influences the entrepreneurial intention, followed by the constructs of the subjective norms and the perception of control. Limitations / implications of the research - The limitations of the study are related to the population because the list of participants includes only graduates of the Empretec Seminar, as well as the fact that it was not considered whether the individuals were temporally close to the triggering event. Practical implications - Entrepreneurial intention is considered as the first step in the process of discovering and exploiting opportunities, which makes it a fundamental part of the understanding of entrepreneurship. The study contributes in diminishing the gap of theoretical and empirical studies on this subject in the Brazilian scenario. Originality / value - The hypothesis that the need for achievement positively influences the entrepreneurial intention has not been accepted, which can occur due to the fact that the psychological characteristics of the entrepreneurs can undergo changes as the entrepreneur moves away from the motivating event of entrepreneurship.